Frederick W. Cooper and Diane Fortenberry (eds). The Minnesota Pylos Project 1990-98 - Dickinson, Oliver (Journal of Greek Archaeology, 2019)
This is a somewhat delayed but extremely welcome volume. It contains a detailed account of the discoveries made in the field and study seasons of the Minnesota Pylos Project. This began with the decision of the Greek Ephoreia of Messenia that a state plan was needed of the remains of the Mycenaean palace excavated by C.W. Blegen on the site often called Ano (surely correctly Epano) Englianos, here most often simply Englianos, identifiable as the legendary Pylos, seat of king Nestor, from the Linear B archive found there. Once work had begun, it quickly became apparent that many widely accepted beliefs about the architectural history of the site were wrong, and a full study of the surviving remains was instituted, including those in various soundings beneath the palace and exploratory trenches in adjacent areas.